Discovery of a Multifunctional Octapeptide from Lingzhi with Antioxidant and Tyrosinase Inhibitory Activity - Yodying Yingchutrakul; Sucheewin Krobthong; Kiattawee Choowongkomon; Phakorn Papan; Pawitrabhorn Samutrtai; Thanisorn Mahatnirunkul; Thitikorn Chomtong; Nitipol Srimongkolpithak; Theeranuch Jaroenchuensiri; Chanat Aonbangkhen (Pharmaceuticals, 2022)
Ganoderma lucidum or Lingzhi is a fungus species widely known as a traditional medicine. Exploring the beneficial peptides by hydrolysis using pepsin and trypsin has been extensively performed to identify new bioactive natural products. A multifunctional peptide that expresses potential scavenging activity and tyrosinase inhibition is valuable in therapeutic and cosmetic applications. This study aimed to identify and investigate the effects of a novel multifunctional peptide from Lingzhi on the melanogenic enzymes in melanoma cells by a targeted-proteomics approach. The multifunctional peptide was de novo sequenced by LC-MS/MS to be NH2-PVRSSNCA-CO2H (octapeptide). This sequence was chemically synthesized by solid-phase peptide synthesis (SPPS). The antioxidant ability of the synthesized octapeptide was measured by the DPPH, ABTS, and FRAP assays. The results showed that the peptide exhibited an antioxidant activity equal to 0.121 ± 0.01 mg equivalent to ascorbic acid, 0.173 ± 0.03 mg equivalent to gallic acid, and 2.21 ± 0.23 mM equivalent to FeSO4, respectively, which is comparable to these well-known antioxidants. The proteomics approach identified a total of 5804 proteins and several pathways involved in the effects of the octapeptide in melanoma cells. Targeted proteomics revealed three specific proteins associated with pigmentation including Rab29, Dct, and Tyrp1. The Rab29 and Dct were upregulated whereas Tyrp1 was downregulated in the octapeptide treatment group. These findings could be used in the understanding of the molecular functions of the multifunctional octapeptide on melanogenic enzymes, supporting its potential as a therapeutic and cosmetic ingredient.